High-flowability copolymerized MX nylon composition and preparation method thereof

By introducing long straight-chain or branched aliphatic diamines and dimethodines into MXD6, and using the synergistic effect of sorbitol-based nucleating agents, the problem of insufficient flow performance of MXD6 materials is solved, better moldability and strength are achieved, and its application scope is expanded.

CN119798985AActive Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510001823.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The flow performance of existing MXD6 materials is insufficient, making it difficult to achieve high content filling or have good moldability and appearance under high filling modification, which limits its application scope.

Method used

By introducing an appropriate amount of other long linear or branched aliphatic diamines into MXD6, and adding 0.1-0.5% dimethoxydiamine in the polymerization stage, combined with the synergistic effect of sorbitol nucleating agents, the fluidity and crystallinity of MX nylon are improved.

Benefits of technology

It significantly improves the flowability and moldability of MX nylon, making the molding of high-glass fiber fill modified products better, improving the strength and appearance performance of the material, and expanding its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798985A_ABST
    Figure CN119798985A_ABST
Patent Text Reader

Abstract

The invention discloses a high-flowability copolymerized MX nylon composition and a preparation method thereof. The composition comprises the following components: a) 30-70 parts of copolymerized MX nylon; b) 30 to 70 parts of glass fiber; c) 0.05 to 0.3 part of a nucleating agent; and d) 0.1-1 part of an antioxidant. The copolymerization modified MX nylon with the viscosity of 1.40-2.00 is selected and matched with the glass fiber with the diameter of about 10 microns, the antioxidant and the nucleating agent to obtain the high-filling modified high-strength high-rigidity modified composition with better formability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high-flow copolymer MX nylon composition and a preparation method thereof. Background Art

[0002] Poly(m-phenylenediamine) MXD6 is a semi-aromatic nylon polymerized from m-phenylenediamine MXDA and adipic acid. Its products are mainly used in packaging and modification fields. At present, the fillers used for MXD6 reinforcement at home and abroad are basically glass fiber, carbon fiber and minerals. It has the advantages of high strength, high rigidity, low creep and low water absorption. It is mainly used in automobile and electrical and electronic parts. The modified filling amount of MXD6 is as high as 60%. Some lubricants are usually added to the formula to make the glass fiber reinforcement have good interface contact with the resin matrix, so that the glass fiber is evenly dispersed, but it also reduces the heat resistance and crystallization performance of the product. High-flowability nylon can improve the impregnation when the glass fiber filling amount is high, and thus can also improve the appearance of the product.

[0003] CN102344670A prepares a high-fluidity high-temperature nylon by adding 1-5% of a high-fluidity additive, but the type and function of the high-fluidity additive are not clear, and the additive is added in the polymerization stage, so the additive has a long heating history and is easily ineffective. Patent CN101148506A improves the fluidity of the product by copolymerizing 0.3-4% of a dendritic polypropylene imine containing terminal amine groups and terephthalic acid into a nylon 6 segment, wherein the molar ratio of the dendritic polypropylene imine to terephthalic acid is 1-4 / 1, and the dendritic polypropylene imine is a polyamine-based product, which is easy to form cross-links and the reaction is uncontrollable.

[0004] How to further improve the flow properties of MXD6 material so that it can be filled with a higher content, or have better formability or appearance under high filling modification, so that it has a wider range of applications, is of great positive significance. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a high-flow copolymer MX nylon composition and a preparation method thereof. The MX nylon prepared by the method of the present application has better fluidity, and the 30-70 parts high glass fiber filled modified product prepared therefrom has better molding.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A high-flow copolymer MX nylon composition comprises the following components in parts by weight:

[0008]

[0009] As a preferred solution, the copolymerized MX nylon monomer components of the present invention include meta-xylylenediamine, adipic acid and other diamines.

[0010] As a preferred embodiment, the other diamines of the present invention contain 0.1-0.5% of di-m-xylylenediamine, based on the mass of the copolymerized MX nylon monomer, and the structural formula is shown in formula a:

[0011]

[0012] As a preferred embodiment, the other diamines of the present invention include one or more of a straight-chain aliphatic diamine having 3 to 18 carbon atoms and / or a branched aliphatic diamine and / or alicyclic diamine.

[0013] As a preferred solution, the amount of the other diamines used in the present invention is 0.1-10% of the total mass of the copolymerized MX nylon monomers.

[0014] As a preferred solution, the molar ratio of all diamine monomers to all dibasic acid monomers in the copolymerized MX nylon monomer is 1-1.001:1.

[0015] As a preferred embodiment, the straight-chain aliphatic diamine of the present invention is selected from one or more of 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine and 1,12-dodecanediamine.

[0016] As a preferred embodiment, the branched aliphatic diamine described in the present invention is selected from one or more of 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2,4-dimethyl-1,6-hexanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2-methyl-1,8-octanediamine, and 5-methyl-1,9-nonanediamine.

[0017] As a preferred solution, the relative viscosity of the copolymerized MX nylon of the present invention is between 1.40-2.00, and the melting point is between 210-235°C.

[0018] As a preferred solution, the preparation method of copolymerized MX nylon described in the present invention is prepared by existing mature polycondensation technology, and a capping agent, a catalyst and water are also added into the preparation method.

[0019] Preferably, the end-capping agent is selected from one or more monoacids or diacids, preferably one or more acetic acid, stearic acid, benzoic acid, adipic acid, sebacic acid, and azelaic acid.

[0020] Preferably, the amount of the end-capping agent is 0.1-5 wt %, preferably 0.3-2 wt %, of the total mass of all diamines and all dibasic acid monomers in the copolymerized MX nylon.

[0021] Preferably, the catalyst is selected from one or more of phosphoric acid, sodium phosphate, sodium hypophosphite and sodium hypophosphite; the amount of the catalyst is preferably 0.1-1wt‰ of the total mass of all diamines and all dibasic acid monomers of the copolymerized MX nylon.

[0022] Preferably, the amount of water used is 10-70 wt % of the total weight of all diamines and all dibasic acid monomers in the copolymerized MX nylon.

[0023] As a preferred solution, the preparation method of the copolymerized MX nylon of the present invention comprises the following steps: adding m-xylylenediamine, adipic acid, other diamines, a catalyst, a capping agent and water into a reaction kettle, heating to 50-120° C. for 30-60 min salt-forming reaction after nitrogen substitution, then transferring to a prepolymerization reaction kettle, then heating to 150-230° C. for 60-120 min prepolymerization reaction, and then continuing to heat to 260-280° C. for 30-120 min melt polycondensation reaction to obtain the copolymerized MX nylon.

[0024] As a preferred embodiment, the nucleating agent of the present invention is selected from sorbitol nucleating agents, and suitable examples include but are not limited to one or more of 1,3-2,4-dibenzylidene sorbitol (DBS), p-methylbenzylidene sorbitol (MDBS), di(p-chlorobenzylidene) sorbitol (CDBS), di(p-ethylbenzylidene) sorbitol (EDBS), 1,3-2,4-di(p-hydroxy)benzylidene sorbitol (DHDBS), 1,3-2,4-di(p-nitro)benzylidene sorbitol (DNDBS), and 1,3-2,4-di(3,4-dimethylbenzylidene)-D-sorbitol (DMDBS).

[0025] As a preferred solution, the diameter of the glass fiber described in the present invention is 9.5-12.5 microns.

[0026] As a preferred solution, the antioxidant described in the present invention is a composite antioxidant of a hindered phenol antioxidant and a phosphate antioxidant, with a weight ratio of 1-2:1.

[0027] The preparation method of the high-flow copolymerized MX nylon composition of the present invention comprises the following steps: according to a proportion, the copolymerized MX nylon is uniformly mixed with a nucleating agent and an antioxidant, and then added to an extruder from a main feeding port of a twin-screw extruder, and then glass fiber is added from a side feeding port of the extruder, the processing temperature is 255-280° C., and extrusion granulation is performed.

[0028] The beneficial effects of the present invention are as follows: the present invention copolymerizes an appropriate amount of other long straight-chain or branched aliphatic diamines with MXD6 nylon, introduces these flexible segments into the rigid MXD6 segment, reduces the melting point and improves the flexibility and fluidity of the MX nylon segment; at the same time, 0.1-0.5% of dimethylbenzene diamine is added in the polymerization stage to polymerize it into the polyamide long chain, and the hydrogen atoms of the polyamide terminal amine group and the secondary amine in the dimethylbenzene diamine can form hydrogen bonds with the oxygen atoms in the ether bond of the sorbitol nucleating agent added in the modification stage, so that the polyamide molecular chain segments are adsorbed or actively attached to the surface of the sorbitol nucleating agent, so that the polyamide molecular chain segments are more stably and orderly arranged on the nucleating agent, thereby improving the crystallinity of the polyamide. The synergistic effect of m-xylylenediamine and sorbitol nucleating agents promotes the uniform distribution of nucleation points while improving the crystallization ability of copolymerized MX nylon, compensating for the problem of slow crystallization caused by copolymerization. At the same time, the nucleating agent also provides additional functions of flow promoter and release agent. Therefore, the flexible chain segment and the nucleating agent synergistically improve the fluidity of the resin.

[0029] On the basis of high-flow copolymer MX nylon, the viscosity and melting point of high-flow copolymer MX nylon are further regulated within a specific range so that it can be fully infiltrated with glass fiber with a high filling amount. Therefore, the modified material prepared from high-flow copolymer MX nylon of the present invention has better molding and excellent properties of high strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the appearance picture of the cracking of the slice in Comparative Example 1.

[0031] Figure 2 This is the appearance picture of the slice with good formability in Example 3. DETAILED DESCRIPTION

[0032] The following examples further illustrate preferred specific embodiments within the scope of the present invention. These examples are merely illustrative and are not intended to limit the scope of the present invention, as many variations of the present invention may be made without departing from the spirit and scope thereof.

[0033] The main raw materials used in the embodiments of the present invention are all obtained from common commercially available raw materials.

[0034] The performance testing method used in the embodiment of the present invention is as follows:

[0035] Relative viscosity: Prepare a concentrated sulfuric acid solution with a nylon chip concentration of 0.01 g / ml, and measure the relative viscosity using an Ubbelohde viscometer.

[0036] Fluidity evaluation: The dried modified particles are extruded into a spiral die using a processed single screw to obtain a spiral sample. The length of the sample is read to evaluate the fluidity of the modified composition.

[0037] Melting point: According to the ISO 11357 test method, the DSC instrument is set to a heating and cooling rate of 10°C / min, a heating and cooling range of 0-300°C, and the peak value of the second heating melting is read as the melting point.

[0038] Mechanical properties test: Mechanical properties are tested according to ISO test standards, tensile strength is tested according to ISO 527-2:2012 standard, tensile speed is 50mm / min. Impact strength is simply supported beam impact strength.

[0039] Preparation Example 1

[0040] Preparation of copolymer MX nylon: 2055.64g (15.093mol) of m-phenylenediamine, 2457.83g (15.955mol) of adipic acid, 90g (0.774mol) of hexamethylenediamine, 22.5g (0.088mol) of di-m-phenylenediamine, 5g of sodium phosphate, 13.95g of adipic acid and 2000g of water were added into a reactor, and after nitrogen substitution, the temperature was raised to 80°C for 30min of salt-forming reaction, and then the temperature was raised to 180°C for 120min of prepolymerization reaction under heat and pressure, and then the temperature was vented to normal pressure, and the temperature was further raised to 260°C for melt polycondensation and nitrogen purging reaction for 90min to obtain copolymer MX nylon with a melting point of 227°C and a relative viscosity of 1.97.

[0041] Preparation Example 2

[0042] Preparation of copolymer MX nylon: 2050.61g (15.057mol) of m-phenylenediamine, 2405.10g (16.458mol) of adipic acid, 235g (1.364mol) of 5-methyl-1,9-nonanediamine, 9.4g (0.037mol) of m-phenylenediamine diacetate, 14.1g of sodium hypophosphite, 23.5g of benzoic acid and 1410g of water were added into a reactor, and after nitrogen substitution, the temperature was raised to 75°C for 55min of salt-forming reaction, and then the temperature was raised to 200°C for prepolymerization reaction at a temperature and pressure of 70min, and then the temperature was vented to normal pressure, and the temperature was further raised to 265°C for melt polycondensation nitrogen purging reaction for 60min to obtain copolymer MX nylon with a melting point of 214°C and a relative viscosity of 1.82.

[0043] Preparation Example 3

[0044] Preparation of copolymer MX nylon: 2373.25g (17.426mol) of m-phenylenediamine, 2586.65g (17.700mol) of adipic acid, 25g (0.215mol) of 3-methyl-1,5-pentanediamine, 15g (0.059mol) of di-m-phenylenediamine, 50g of phosphoric acid, 100g of azelaic acid and 3500g of water were added into a reactor. After nitrogen substitution, the temperature was raised to 120°C for 45min of salt-forming reaction, and then the temperature was raised to 230°C for 60min of heat and pressure prepolymerization reaction, and then the temperature was vented to normal pressure, and the temperature was continued to be raised to 280°C for melt condensation nitrogen purge reaction for 35min to obtain copolymer MX nylon with a melting point of 233°C and a relative viscosity of 1.41.

[0045] Preparation Example 4

[0046] Preparation of copolymer MX nylon: 1883.92g (13.833mol) of m-phenylenediamine, 2431.40g (16.637mol) of adipic acid, 480g (2.786mol) of 1,10-decanediamine, 4.8g (0.019mol) of di-m-phenylenediamine, 24g of sodium hypophosphite, 48g of stearic acid and 480g of water were added into a reactor, and after nitrogen substitution, the temperature was raised to 50°C for 60min of salt-forming reaction, and then the temperature was raised to 150°C for 90min of prepolymerization reaction under heat and pressure, and then the temperature was vented to normal pressure, and the temperature was further raised to 270°C for melt condensation nitrogen purging reaction for 120min to obtain copolymer MX nylon with a melting point of 210°C and a relative viscosity of 1.65.

[0047] Preparation of Comparative Example 5

[0048] According to the formulation of Example 3, without adding m-xylylenediamine and reducing the corresponding amount of adipic acid by 8.57 g (0.059 mol), polymerization was carried out to obtain copolymer MX nylon with a melting point of 235° C. and a relative viscosity of 1.41.

[0049] Preparation of Comparative Example 6

[0050] According to the formulation of Preparation Example 3, 3-methyl-1,5-pentanediamine was not added and the corresponding amount of adipic acid was reduced by 31.44 g (0.215 mol), and copolymer MX nylon was obtained by polymerization with a melting point of 229° C. and a relative viscosity of 1.41.

[0051] According to the proportion of each group shown in the table below, the copolymerized MX nylon is mixed with the nucleating agent, antioxidant and glass fiber, and then added to the extruder from the main feed port of the twin-screw extruder. Then the glass fiber is added from the side feed port of the extruder. The processing temperature is set in the range of 255-280℃, and finally extruded into granules, and then the processing test is carried out.

[0052] Table 1 Example and Comparative Example Experimental Formula

[0053]

[0054] Table 2 Test results of embodiments and comparative examples

[0055] sample Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength MPa 220 280 300 320 200 210 210 Bending strength MPa 360 400 440 480 320 350 340 Notched impact strength J / m2 15 14 17 16 5 8 9 Spiral length 530 480 460 410 390 395 400 Slice Formability good good good good Cracking Cracking Cracking

[0056] It can be seen from the examples that as the filling amount increases, the mechanical properties of the product gradually increase; it can be seen from the comparative examples and the examples that the MX modified composition obtained by the present invention has higher strength and better formability.

[0057] The above embodiments are only for illustrating the technical concept and features of the present invention, and cannot be used to limit the protection scope of the present invention. Any changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-flow copolymer MX nylon composition comprising the following components in parts by weight:

2. The composition according to claim 1, characterized in that The copolymerized MX nylon monomer components include meta-xylylenediamine, adipic acid and other diamines; the other diamines include di-meta-xylylenediamine.

3. The composition according to claim 2, characterized in that The amount of the di-m-xylylenediamine used is 0.1-0.5%, based on the mass of the copolymerized MX nylon monomer.

4. The composition according to claim 2 or 3, characterized in that The other diamines further include one or more of a linear aliphatic diamine having 3 to 18 carbon atoms and / or a branched aliphatic diamine and / or alicyclic diamine.

5. The composition according to any one of claims 2 to 4, characterized in that The amount of the other diamines used is 0.1-10% of the mass of the copolymerized MX nylon monomer.

6. The composition according to claim 4, characterized in that The straight-chain aliphatic diamine is selected from one or more of 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine; the branched aliphatic diamine is selected from one or more of 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2,4-dimethyl-1,6-hexanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2-methyl-1,8-octanediamine, and 5-methyl-1,9-nonanediamine.

7. The composition according to any one of claims 1 to 6, characterized in that The relative viscosity of the copolymerized MX nylon is between 1.40 and 2.00, and the melting point is between 210 and 235°C.

8. The composition according to any one of claims 1 to 7, characterized in that The preparation method of copolymerized MX nylon comprises the following steps: adding m-xylylenediamine, adipic acid, other diamines, a catalyst, a capping agent and water into a reaction kettle, heating to 50-120° C. after nitrogen substitution for salt-forming reaction for 30-60 min, then transferring to a prepolymerization reaction kettle, then heating to 150-230° C. for prepolymerization reaction for 60-120 min, and then continuing to heat to 260-280° C. for melt polycondensation reaction for 30-120 min to obtain copolymerized MX nylon.

9. The composition according to claim 8, characterized in that The end-capping agent is selected from one or more monoacids or diacids, preferably one or more acetic acid, stearic acid, benzoic acid, adipic acid, sebacic acid, and azelaic acid.

10. A method for preparing the composition according to any one of claims 1 to 9, comprising the following steps: According to the proportion, the copolymerized MX nylon is evenly mixed with the nucleating agent and the antioxidant, and then added into the extruder from the main feeding port of the twin-screw extruder, and then the glass fiber is added from the side feeding port of the extruder. The processing temperature is 255-280° C. and extrusion granulation is performed.

Citation Information

Patent Citations

  • Flame-retardant polyamide resin composition and molded article

    CN101595183A

  • High-fluidity nylon

    CN102344670A

  • Modified elastomer for MX (M Xylene) nylon and preparation method thereof

    CN103087512A

  • Thermoplastic resin composition, resin molded article, and method for producing resin molded article having plated layer attached thereto

    CN104583331A

  • Method for granulating polyamide or polyamide composition

    CN105940043A